PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR-DASAR MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS KELAS X SMK NEGERI 1 TELUK MENGKUDU - Gustina Pandiangan, Deka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Think-Pair-Share (TPS) learning model on student learning outcomes in the "Fundamentals of Office Management and Business Services" subject for Grade X students at SMK Negeri 1 Teluk Mengkudu. The study was motivated by low student motivation and learning outcomes with many students scoring below the Minimum Mastery Criteria (KKM) of 75 resulting in a 62.5% non-mastery rate attributed to the dominance of conventional (lecture-based) teaching methods. A quantitative approach with a quasi-experimental design (Pretest-Posttest Control Group Design) was employed. The study population comprised all 64 Grade X Office Management students from the 2025/2026 academic year, selected via a saturated sampling technique and divided into two groups: Class X ADP 1 served as the experimental group (32 students) taught using the Think-Pair-Share model, while Class X ADP 2 served as the control group (32 students) taught using the lecture method. Data collection utilized multiple-choice learning outcome tests (pretest and posttest). Data analysis was conducted using simple linear regression and t-tests. The results showed an increase in the experimental group's average score from 62.75 (pretest) to 81.5 (posttest). Regression analysis yielded the equation Y = 70.72 + 0.1718X with a coefficient of determination (R-squared) of 0.436, indicating that the Think-Pair-Share model contributed 43.6% to student learning outcomes. Hypothesis testing revealed a calculated t-value of 4.818, which exceeded the t-table value of 1.697 at a significance level of alpha = 0.05 (p = 0.000 < 0.05). Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, demonstrating that the application of the Think-Pair-Share learning model has a positive and significant effect on student learning outcomes in the "Fundamentals of Office Management and Business Services" subject for Grade X students at SMK Negeri 1 Teluk Mengkudu.